Credit derivatives and bank credit supply - Beverly Hirtle (Federal Reserve Bank of New York, 2007)
Credit derivatives are the latest in a series of innovations that have had a significant impact on credit markets. Using a micro data set of individual corporate loans, this paper explores whether use of credit derivatives is associated with an increase in bank credit supply. We find evidence that greater use of credit derivatives is associated with greater supply of bank credit for large term loans—newly negotiated loan extensions to large corporate borrowers—though not for (previously negotiated) commitment lending. This finding suggests that the benefits of the growth of credit derivatives may be narrow, accruing mainly to large firms that are likely to be “named credits” in these transactions. Further, the impact is primarily on the terms of lending—longer loan maturity and lower spreads—rather than on loan volume. Finally, use of credit derivatives appears to be complementary to other forms of hedging by banks.
Keywords: G21; G32; 330; credit derivatives; risk management; credit supply; bank lending; Credit Default Swap; Finanzderivat; Kreditrisiko; Risikomanagement; Kreditgeschäft; USA